Membrane damage and recovery associated with growth delay induced by near-UV radiation in Escherichia coli K-12 - Pizarro, Ramón A.; Orce, Luis V. (Pergamon Press Ltd., 1988)
Fil: Pizarro, Ramón A. Comisión Nacional de Energía Atómica; Argentina